Does removal of aids/devices and help make a difference in the Childhood Health Assessment Questionnaire disability index?. Issue 01 (16th February 2009) - Saad-Magalhães, C; Pistorio, A; Ravelli, A; Filocamo, G; Viola, S; Brik, R; Mihaylova, D; Cate, R ten; Andersson-Gare, B; Ferriani, V; Minden, K; Hashkes, P; et al.
Abstract : Objective: To assess whether the removal of aids/devices and/or help from another person in the Childhood Health Assessment Questionnaire (C-HAQ) leads to a significant change in the disability index (DI) score and responsiveness in juvenile idiopathic arthritis (JIA). Methods: Changes in the C-HAQ DI score in a cross-sectional sample of 2663 children with JIA and in 530 active patients with JIA in a trial of methotrexate (MTX) were compared. Results: Patients in the MTX trial had higher disease activity and disability than the cross-sectional sample. The frequency of aids/devices (range 1.2–10.2%) was similar between the two samples, while help (range 5.3–38.1%) was more frequently used in the MTX group. Correlation between disease severity variables and the two different C-HAQ DI scoring methods did not change substantially. There was a decrease in the C-HAQ DI score for both the cross-sectional (mean score from 0.64 with the original method to 0.54 without aids/devices and help, p<0.0001) and the MTX sample (mean score from 1.23 to 1.07, p<0.0001). A linear regression analysis of the original C-HAQ DI score versus the score without aids/devices and help demonstrated the substantial overlap of the different scoring methods. Responsiveness in the responders to MTX treatment did not change with the different C-HAQ DI scoring methods (range 0.86–0.82). Conclusion: The removal of aids/devices and help from the C-HAQ does not alter the interpretation of disability at a group level. The simplified C-HAQ is a more feasible and valid alternative for the evaluation of disability in patients with JIA.